Outer membrane proteins and cell surface structure of Selenomonas ruminantium. - Kamio, Y (1980)
The protein compositions of the membrane preparations from Selenomonas ruminantium grown in glucose or lactate medium were determined by sodium dodecyl sulfate- and two-dimensional (first, isoelectric focusing; second, sodium dodecyl sulfate) polyacrylamide slab gel electrophoresis. The outer membrane from both glucose- and lactate-grown cells contained two major proteins with apparent molecular weights of 42,000 and 40,000. These proteins existed as peptidoglycan-associated proteins in the outer membrane. The critical temperature at which they were dissociated completely into the monomeric subunits of 42,000 and 40,000 daltons was found to be 85 degrees C. The amount of each protein varied considerably depending upon the cultural conditions. The absence of the lipoprotein of Braun in S. ruminantium was suggested in our preceding paper (Y. Kamio, and H. Takahashi, J. Bacteriol. 141:888--898, 1980), and the possible absence of the protein components corresponding to the Braun lipoprotein in this strain was confirmed by electrophoretic analysis of the outer membrane and the lysozyme-treated peptidoglycan fractions. Examination of the cell surface of S. ruminantium by electron microscopy showed that the outer membrane formed a wrinkled surface with irregular blebs, some of which pinched off forming vesicles of various sizes. Rapid cell lysis occurred with the addition of a low level of lysozyme to the cell suspension. These findings led us to conclude that the physiological and morphological properties of this strain were similar to those of "deep rough" and mlp or lpo mutants of Escherichia coli K-12, respectively.